ULTIMUM REMEDIUM PRINCIPLES IN CRIMINAL DECISIONS IN CREATING RESTORATIVE JUSTICE - Rina Melati Sitompul; Andi Maysarah (STIH Putri Maharaja, 2021)
Principles are the heart of law, where their application becomes a form of awareness for judges in making decisions. The concept of this study analyzes the extent to which the ultimum remedium principle becomes the basic principle of judges to remove children from prison. Because the ultimate goal of achieving this principle is to encourage resolution of the problem by involving perpetrators, victims, and other parties in seeking a just solution by emphasizing recovery back to its original state. The form of this research is a normative juridical study with a descriptive analytical approach, which takes a sample of 7 (seven) verdicts in child criminal cases in 2 (two) jurisdictions, namely the Medan District Court and the Stabat District Court. In the conclusion of the results formulating the provisions of Law no. 11 of 2012 becomes a form of certainty to make it easier for judges to make the best decisions for children as the principle of ultimum remedium principle, although there are still some judges acting based on the theory of retaliation when concluding responsibility for children's mistakes.